Day‐to‐day variability of porcine lente, insulin glargine 300 U/mL and insulin degludec in diabetic dogs. (9th July 2021) - Miller, Michelle; Pires, Jully; Crakes, Katti; Greathouse, Rachel; Quach, Nina; Gilor, Chen
Abstract: Background: Day‐to‐day variability impacts safety of insulin therapy and the choice of monitoring strategies. Side‐by‐side comparisons of insulin formulations in diabetic dogs are scarce. Hypothesis/Objectives: Insulin glargine 300 U/mL (IGla300) and insulin degludec (IDeg) are associated with less day‐to‐day glucose variability compared to porcine lente (PL) in diabetic dogs. Animals: Seven intact male purpose‐bred beagles with toxin‐induced diabetes. Methods: In this repeated measured study, PL, IGla300 and IDeg were compared in 2 phases: once‐daily (q24h) and twice‐daily (q12h) administration. Interstitial glucose concentrations (IG) were measured continuously throughout the study. For each formulation, maximal q24h dose was determined using the same algorithm (while avoiding hypoglycemia) and then maintained for 72 hours. In phase 2, 70% of the maximal q24h dose was administered q12h and maintained for 5 days regardless of hypoglycemia. Coefficient of variation (CV) and glycemic variability percentage (GVP) were calculated to determine day‐to‐day and intraday variability, respectively. Results: There was no difference in day‐to‐day variability between PL, IGla300, and IDeg in the q24h phase. In the q12h phase, day‐to‐day variability was higher ( P  = .01) for PL (CV = 42.6 ± 6.8%) compared to IGla300 and IDeg (CV = 30.1 ± 7.7%, 25.2 ± 7.0%, respectively). The GVP of PL was lower ( P  = .02) compared to IGla300. There was no difference between PL, IGla300 and IDeg in %time IG < 70 mg/dL. Conclusions and Clinical Importance: Insulin degludec and IGla300 administered q12h were associated with lower day‐to‐day variability, which might be advantageous in minimizing monitoring requirements without increasing the risk of hypoglycemia.